2020
DOI: 10.1001/jamaneurol.2020.1087
|View full text |Cite
|
Sign up to set email alerts
|

Use of Multimodal Imaging and Clinical Biomarkers in Presymptomatic Carriers of C9orf72 Repeat Expansion

Abstract: Key Points Question Can metabolic brain changes be detected in presymptomatic individuals who are carriers of a hexanucleotide repeat expansion in the C9orf72 gene (preSxC9) using time-of-flight fluorine 18–labeled fluorodeoxyglucose positron emission tomographic imaging and magnetic resonance imaging, and what is the association between the mutation and clinical and fluid biomarkers of amyotrophic lateral sclerosis and frontotemporal dementia? … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
48
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 50 publications
(56 citation statements)
references
References 54 publications
1
48
0
Order By: Relevance
“…A recent study of presymptomatic C9orf72 carriers also found significant hypometabolism in the insular cortices, central opercular cortex, basal ganglia, and thalami compared to healthy controls, that preceded any significant elevation of neurofilament levels. ( De Vocht et al, 2020 ) These regions were consistent with our findings, although we additionally showed significant hypometabolism in the inferior parietal lobe and the adjacent regions such as the posterior and isthmus cingulate gyri. In particular, the parietal involvement was also shown in a perfusion MRI-based study of presymptomatic C9orf72 carriers.…”
Section: Discussionsupporting
confidence: 92%
“…A recent study of presymptomatic C9orf72 carriers also found significant hypometabolism in the insular cortices, central opercular cortex, basal ganglia, and thalami compared to healthy controls, that preceded any significant elevation of neurofilament levels. ( De Vocht et al, 2020 ) These regions were consistent with our findings, although we additionally showed significant hypometabolism in the inferior parietal lobe and the adjacent regions such as the posterior and isthmus cingulate gyri. In particular, the parietal involvement was also shown in a perfusion MRI-based study of presymptomatic C9orf72 carriers.…”
Section: Discussionsupporting
confidence: 92%
“…106 Studies that investigated both NfL and pNfH suggested that pNfH was better at discriminating ALS from other motor neuron diseases, 107 thought NfL was better at reflecting disease severity and progression. 108,109 Nevertheless, these studies were not powered or aimed at comparing the performance of the Figure 2. Interpretation of NfL levels in adult and elderly patients.…”
Section: Alzheimer Diseasementioning
confidence: 99%
“…Similar to NfL, increased pNfH levels have been observed prior to symptom onset, 102 discriminated ALS from ALS mimics 99 and was associated with the disease progression rate 106 . Studies that investigated both NfL and pNfH suggested that pNfH was better at discriminating ALS from other motor neuron diseases, 107 thought NfL was better at reflecting disease severity and progression 108,109 . Nevertheless, these studies were not powered or aimed at comparing the performance of the two biomarkers and confirmatory studies are needed.…”
Section: Blood Nfl In Neurological Diseasesmentioning
confidence: 99%
“…The majority of imaging studies in ALS explored the underpinnings of the most commonly affected neuropsychological domains (233,244), such as the substrate of verbal fluency deficits, executive dysfunction, and behavioral impairment, but with the recognition of the relatively high prevalence of impairments in social cognition, memory deficits, and of apathy, the focus of imaging studies is likely to gradually shift (12,(245)(246)(247)(248)(249). Imaging changes in ALS are typically solely interpreted based on genetic and clinical profiles, and seldom correlated with other markers such biofluid markers (250)(251)(252). The radiological patterns identified by various imaging studies are largely congruent with the distribution of pathological TDP-43 (pTDP-43) aggregates in extra-motor brain regions (253)(254)(255)(256)(257).…”
Section: Amyotrophic Lateral Sclerosismentioning
confidence: 99%